Employer Branding sebagai Strategi untuk Meningkatkan Intention to Apply di Kalangan Generasi Z - Lubana Nataghain AlMuhdhar; Nida Hasanati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Competition in acquiring young talent is increasing, so employer branding strategies are an important element for organizations in attracting the interest of generation Z. As digital natives, generation Z has different characteristics and expectations, including the need for career development, work-life balance, organizational reputation, and an inclusive work culture (Smith, 2022). In the midst of global competition and the increasingly dominant use of digital technology in the job search process, companies are required to build an authentic and relevant employer image in order to increase the attractiveness of their talents. Previous research has shown that employer branding has a significant effect on the interest in applying for jobs for generation Z, either directly or through mediating factors such as organizational reputation and person-organization fit (Backhaus & Tikoo, 2004; Jiang & Iles, 2024). Based on this phenomenon, this study aims to analyze the influence of employer branding on the interest in applying for jobs of Generation Z and examine the role of organizational reputation and person organization fit as a mediation variable. The study used a quantitative approach with a survey method of Generation Z respondents who were looking for a job, then analyzed using multiple regression and bootstrapping mediation test. The results of the study show that employer branding has a positive and significant effect on the interest in applying for jobs for generation Z, and this influence is stronger when the reputation of the organization and the person-organization fit plays the role of mediator. These findings affirm the importance for organizations to build a positive image, provide an inclusive work culture, and highlight the value match between companies and applicants in order to be able to compete in the fight for young talent in the digital era.